A novel technique leading to complete sensory and motor recovery across a long peripheral nerve gap - Reyes, Onix; Sosa, Iván J.; Santiago, José; Kuffler, Damien P. (Puerto Rico Health Sciences Journal, 2007)
Sensory nerve grafts are the “gold standard” for inducing neurological recovery in peripheral nerves with a gap. However, the effectiveness of sensory nerve grafts is variable, generally not leading to complete sensory and motor recovery, with good recovery limited to gaps shorter than 2 cm, and the extent of recovery decreasing with increasing graft length. An alternative technique using a conduit filled with pure fibrin to bridge a nerve gap leads to only limited neurological recovery. We tested the effectiveness of a novel nerve repair technique in which a 5-cm long radial nerve gap was repaired using two sural nerve graft surrounded by a collage tube filled with pure fibrin. By 1½ years post surgery, the patient recovered complete sensory and motor function. In conclusion, this study suggests that the combination of pure fibrin surrounding sural nerve grafts is responsible for inducing the extensive neurological recovery induced by either pure fibrin or sural grafts alone. This technique is presently being tested in a clinical trial.